PENEGAKAN HUKUM TERHADAP TINDAK PIDANA EKSPLOITASI SEKSUAL ANAK DI WILAYAH HUKUM KOTA DUMAI - Tamara Aryani Siregar; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Children are the next generation of national ideals, have a strategic role inensuring the existence of the nation and state and getting protection from parents,family, society, nation and state. But now there are still many problems found inchildren, one of which is sexual exploitation of children. This is very alarming wherethere is no strict treatment from the police, law enforcement in the field of sexualexploitation of children is still ineffective in view of the increasing cases of sexualexploitation of children, but they are reluctant to make reports due to public doubtsabout the police.This research is sociological research which is to see the influence of positive lawon people's lives. This research was conducted in the jurisdiction of the Dumai CityResort Police, while the population and sample were all parties related to the problemsexamined in this study, data sources used, primary data, secondary data and tertiarydata, data collection techniques in this study were carried out through observation,interview and literature review.From the results of the research conducted, it can be concluded, First, preventiveand repressive law enforcement. Second, the obstacles faced are internal factors,internal factors such as the number of police personnel, the ability of personnel, thebudget of the police institution, limited facilities and infrastructure. The external factorin the form of children is not realizing that he is a victim, fear of not obeying what wasordered by the perpetrators, public distrust of law enforcement, low awareness of thevictims and lack of public awareness of the law and problems of sexual exploitation ofchildren. Third, efforts to overcome barriers, namely fixing internal deficiencies,namely by adding personnel and increasing police capabilities by holding training andeducation on a regular basis, managing finances and adding facilities andinfrastructure to existing needs, and fixing external deficiencies, namely providingunderstanding education towards children that what they do endangers them, restoreschildren's trust through treatment by psychologists, instills a religious sense of fear ofsin, restores the community's trust in the police and increases public awareness of theimportance of law and the importance of child protectionKeywords: Law Enforcement – Crime - Sexual Exploitation of Children